Land use dynamics and socio-economic impacts of wetlands in the Oti plain in the face of climate change - Lamboni, Lardja; Belem, Maïmounata (International Journal of Environment, Agriculture and Biotechnology, 2024)
Wetlands are one of Togo's most important natural resources. However, human pressures on these already vulnerable environments are contributing to a reduction in their surface area and, consequently, to a loss of biodiversity. The aim of this study is to assess the vulnerability of wetlands to climate change through a diachronic analysis of changes in climatic parameters over the period 1970-2021. To do this, we first mapped land use units from 1987 to 2019 in order to identify the various pressures on wetland ecosystems in the Oti plain in northern Togo (Ramsar site of the Oti-Kéran-Mandouri protected areas). Secondly, we identified wetland degradation factors and the socio-economic impacts of this degradation on local populations. The results show that the surface area of the natural land-use units of the Oti plain has declined over the last thirty years. Over the same period, the climate in the area has been highly variable, alternating between dry and wet periods, with a general trend towards lower rainfall and higher temperatures. The effects of this climate change, coupled with human-induced degradation factors, are having a negative impact on the socio-economic situation of local populations. The Participatory Analysis of Powerty and Livelihood Dynamic (PAPOLD) also enabled farmers to be classified into three prosperity classes (Poor, Moderately Well Off and Well Off). The results provide a decision-making tool for sustainable, participatory management of the wetlands of the Oti plain.